Inventarisasi Tumbuhan Famili Euphorbiaceae Di Kelurahan Mekar Mulya, Kecamatan Panyilekan, Kota Bandung - Agnie Airul Akira; Alvi Arumi Fadila; Aprilia Khoirunnisa Emnur; Ateng Supriyatna (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Euphorbiaceae is a group of plants often referred to as the sap tribe. Euphorbiaceae can be used as food, firewood, medicinal plants, building materials and also as ornamental plants. This study aims to determine the distribution of species from the Euphorbiaceae family located in Mekar Mulya Village, Panyileukan District, Bandung City. The method used, namely the direct exploration method by observing morphological characteristics, species, the number of each species and distribution patterns. The results showed that there were 6 species of plants included in the Euphorbiaceae family, including 21 individuals of Euphorbia milli, 52 individual of Sauropus androgynous, 108 individuals of Manihot esculenta, 7 individuals of Codiaeum variegatum, 3 individuals of Euphorbia tithymaloides and 6 individuals of Acalypha siamenis.